Meditation-Induced Psychosis: Trigger and Recurrence - Sulochana Joshi; Anusha Manandhar; Pawan Sharma (Case Reports in Psychiatry)
Meditation is regarded as a self-regulation approach to manage emotions. Meditation has a beneficial effect on mental health. Different kinds of meditation are practiced in many religions and cultures for the general wellbeing of an individual. However, meditation-related experiences and negative effects of meditation are not uncommon. Meditation-induced psychosis has been reported in the past. Here, we present a case of a 33-year-old male patient who developed acute and transient psychosis twice after meditation and discuss the role of meditation as a precipitating factor to psychosis.